2019
DOI: 10.1038/s41598-019-38545-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent autonomic dysfunction and bladder sensitivity in primary dysmenorrhea

Abstract: Menstrual pain, also known as dysmenorrhea, is a leading risk factor for bladder pain syndrome (BPS). A better understanding of the mechanisms that predispose dysmenorrheic women to BPS is needed to develop prophylactic strategies. Abnormal autonomic regulation, a key factor implicated in BPS and chronic pain, has not been adequately characterized in women with dysmenorrhea. Thus, we examined heart rate variability (HRV) in healthy (n = 34), dysmenorrheic (n = 103), and BPS participants (n = 23) in their lutea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
(62 reference statements)
0
14
1
Order By: Relevance
“…It is also notable that at baseline prior to their operation, these patients did not have differences in HR or BP measurements compared to controls. These findings contrast with results from several groups that reported resting HR and BP are higher in those with IC/BPS (25)(26)(27).…”
Section: Systemic Changes In Ic/bps Patients Suggestive Of Autonomic Nervous System Changescontrasting
confidence: 99%
See 1 more Smart Citation
“…It is also notable that at baseline prior to their operation, these patients did not have differences in HR or BP measurements compared to controls. These findings contrast with results from several groups that reported resting HR and BP are higher in those with IC/BPS (25)(26)(27).…”
Section: Systemic Changes In Ic/bps Patients Suggestive Of Autonomic Nervous System Changescontrasting
confidence: 99%
“…The vagus nerve (parasympathetic) is responsible for decreasing the speed of the heart rate, while sympathetic tone increases the speed of the heart and raises blood pressure. Therefore, it is notable that those with IC/BPS have been found to have an elevated resting heart rate ( 25 , 26 ) and diastolic blood pressure ( 26 ) at rest. Elevations in resting heart rate (without blood pressure changes) have also been seen prior to, while undergoing, and after undergoing a variety of mental stress models and was unrelated to perceived stress changes ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“… 8 In another study, abnormal autonomic activity was identified in women with dysmenorrhea even 2 weeks after menses. 13 These studies highlight the importance of understanding how chronic pain develops and how to treat it. 8 , 13 Additionally, a British study of 1671 reproductive-aged women found that of the 24% of women with CPP, 11% also reported dysmenorrhea, 1.4% reported dyspareunia (painful intercourse), and 8% reported all three conditions.…”
Section: Potential Life-course Impact Of Endometriosismentioning
confidence: 99%
“… 13 These studies highlight the importance of understanding how chronic pain develops and how to treat it. 8 , 13 Additionally, a British study of 1671 reproductive-aged women found that of the 24% of women with CPP, 11% also reported dysmenorrhea, 1.4% reported dyspareunia (painful intercourse), and 8% reported all three conditions. 14 Women with CPP had lower scores in QoL related to physical and mental health and greater sleep-related difficulties (eg, difficulty falling asleep or staying asleep) compared with the women who had dysmenorrhea only.…”
Section: Potential Life-course Impact Of Endometriosismentioning
confidence: 99%
See 1 more Smart Citation